Shoot generation and callus induction of Dioscorea hispida Dennst by different plant growth hormones and basal media - Nor Hasima, Mahmod; Zakiah, Mustapha; Ahmad Hilman Ariffin, Husni (Penerbit Universiti Sultan Zainal Abidin, 2020)
Dioscorea hispida Dennst produces tuber which possess valuable medicinal properties but unsustainable harvesting has led to its reduction. The plant propagates slowly because of its low tuber sprouting rate. In average, Dioscorea hispida Dennst tubers took approximately 60 d to break dormancy and sprout. Hence, callus culture is proposed as a possible efficient type of culture for manipulation of this species. In the present study, calli were induced from stem segments to evaluate callus culture potential of Dioscorea hispida Dennst. Results indicate that the combination of 1 mgL-1 naphthaleneacetic acid (NAA), 1 mgL-1 6- benzylaminopurine (BAP) and 0.5 mgL-1 2,4-dichlorophenoxyacetic acid (2, 4-D) in Gamborg (B5) medium improved callus multiplication and differentiation in the stem culture as opposed to those in Murashige and Skoog (MS) medium. The findings from the present study provide the basis of callus culture protocol for stem explant of Dioscorea hispida Dennst with B5 being the more effective basal medium.